Analysis of Radiation Dose Rate and Evaluation of Whole Body Scan SPECT/CT Images in Thyroid Carcinoma Radioablation Patients Using Radioisotope 131I (International Journal of Scientific Research in Science and Technology, 2024)
The incidence rate of thyroid carcinoma shows an increasing trend from year to year. One method for treating thyroid carcinoma is radioablation therapy using 131I. The use of 131I must be carried out in accordance with radiation safety regulations to avoid undesirable radiation dose rates. Therefore, research was conducted to analyze the radiation dose rate emitted by patients, obtain the relationship between body mass index (BMI) and the emitted dose rate, and evaluate whole body scan images of Single-Photon Emission Computed Tomography (SPECT/CT) of thyroid carcinoma radioablation patients. The research was carried out by measuring the patient’s radiation dose rate using a surveymeter. The sample used was 53 patients who met the inclusion criteria and were not included in the exclusion criteria. The patient is isolated until it is safe to leave the hospital, then the therapy is evaluated by means of a whole body scan using SPECT/CT. Region of Interest (ROI) was carried out on the thyroid, stomach, liver, large intestine and bladder. On the third day the patient’s dose rate value was below 70 μSv/h so that the patient could go home safely in accordance with radiation protection regulations. The average dose rate value for obese patients was higher compared to patients with low, normal and excess BMI. The high organ radiation count value for whole body SPECT/CT scan patients is caused by several factors such as the absorption of 131I by organs and the buildup of radioisotopes in organs.